ISLAM, HAK DAN KESEHATAN REPRODUKSI - Waliko Waliko (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
Islam is often preceived as a religion that give lack attention to the rights ofreproduction for women. Islam is considered as religion that views reproduction aswomen’s duty and never views women’s rights in relation to reproduction. In onehand, as the functions of reproduction, a woman has some duties to be pregnant, givebirth, breast feed, and take care of her children as well as other duties related tothese. But, on the other hand, woman’s rights related to reproduction are oftenignored. Moreover, conventinal interpretation often leads muslims to have aperception that choosing a marital partner, enjoying sexual intercouse, havingchildren, deciding when to be pregnant, and the decision to divorce are not parts ofwoman’s rights. All of these decisions are commonly hold by a man. Such problemoften occurs in Majlis Ta’lim in Banyumas Regency, especially one in Cikembulan,District of Pekuncen, which most of the members are women.This is a qualitative research mostly depending on the ability to observe,interview, and interpret. The analysis used in this research was qualitative dataanalysis using verstehen model. The research findings are: generally memebers ofSalma al-Fareeha assume that the right to decide pregnancy and to have children isthe right of husband because it is the husband who is responsible to work (nafkah) tosupport the family. Although some of them said that they made the decisiontogether, some others said that the husband decide what contraception to be used bythe wife. This fact shows that the ideals and the reality of the rights of reproductionin the majlis ta’lim were influenced by their level of understanding the religion,education, experience, and age. The younger they are, they realize more about theimportance of reproduction health for women.